Understanding service users and other stakeholders' engagement in maternal and newborn health services research: A systematic review of evidence from low- and middle-income countries. - Devendra Raj Singh; Rajeeb Kumar Sah; Bibha Simkhada; Zoe Darwin (PLoS ONE)
Background Stakeholder engagement is widely considered democratic, transparent, and essential in the shared decision-making process for improving health services. However, the integrated evidence of stakeholders' engagement activities in maternal and newborn health (MNH) services in the context of low- and middle-income countries (LMICs) is lacking. Therefore, this review aims to generate synthesised evidence of different practices for stakeholder engagements, characteristics of stakeholder engagements and outcomes of stakeholder engagements in improving the MNH services uptake and delivery. Methods The systematic review reporting followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) checklist. The literature was searched in PubMed, CINAHL, PsycINFO, Science Direct and Scopus databases. The identified records were screened using Covidence software, and data were extracted from included records using a predefined template. The mixed methods appraisal tool was used to assess the quality of the included studies. The spectrum of stakeholder engagement provided by the International Association for Public Participation (IAP2) was used as a guiding framework for synthesising the evidence related to stakeholder engagement. Results A total of 1473 records were identified through the initial search after removing the duplicates. Twenty-six studies were included in the final review. The review results related to service users and other stakeholders' engagement are presented under three overarching themes: (i) Methods and contexts of stakeholders' engagement, (ii) Outcomes of stakeholders' engagement, and (iii) Facilitators and barriers to stakeholders' engagement. Conclusion Various participatory approaches were utilised to engage the service users and other stakeholders in improving MNH service uptake and delivery. A wide range of service user- and provider-led outcomes were identified due to stakeholder engagement. Trial registration PROSPERO registration number: CRD42022314613.